Pendampingan Strategi Belajar Pada Anak Usia Dini yang Mengalami Keterlambatan Berbicara (Speech Delay) di Raudhatul Atfal Muslimat Nahdatul Ulama 127 Ngrogung Kecamatan Ngebel Kabupaten Ponorogo - Wilda Mukhib Muttaqin; Rinesti Witasari (Social Science Academic, 2023)
The benefits of learning strategy assistance for early childhood who experience speech delays are very important to support their optimal development. Learning strategy support methods for early childhood with speech delays are typically holistic, tailored to the child's needs, and involve multiple stakeholders. These include using games to enhance interaction and communication during learning, and using multisensory methods that integrate the senses (sight, hearing, and touch) into learning activities. As a result, children are more interested in interacting with friends or teachers because the game is fun. Children understand information more easily because it involves more than one sense.